A simple method based for computing crack shapes. (January 2016) - Peng, D.; Huang, P.; Jones, R.; Bowler, A.; Edwards, D.
Abstract: The growth of cracks from small naturally occurring material discontinuities plays a major role in the operational lifespan of aircraft structures. Calculating the life of an airframe structure requires the determination of the crack path(s) which for complex real life geometries can often be highly complex. This paper presents a simple method based on finite element analysis for estimating the crack growth path. The analysis is based on an element removal approach and uses the major principal stress as the failure criteria. Evolution strategies are derived from the biological process of evolution. Three examples are presented demonstrating the utility of the proposed technique. Highlights: A simple method based on an element removal approach for estimating the 3D crack growth path Three examples are presented that demonstrate the utility of the proposed technique. A further advantage is that remeshing is not necessary since cracks are not explicitly modelled.